Situation Report: Baltic Area, 31 May 1989 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Poll on Independence and Political Parties / by Toomas Ilves Latvian Exile Leaders Meet in France with Representatives of People's Front of Latvia / by Dzintra Bungs Lithuania Declares Its Sovereignty / by Saulius Girnius The Elimination of the Last Blank Spots in Lithuanian History / by Kestutis Girnius